Respuesta :

Answer:

1

Step-by-step explanation:

[tex]h {}^{ - 1} ( - 1)[/tex]

means that what is the value of the inverse function of h(x) when x=-1. The inverse function x and y values swap with original functions. When x=1, y=-1 so the inverse of that will be when x=-1, y=1.

Applying the inverse function concept, it is found that [tex]h^{-1}(-1) = 1[/tex]

The inverse function [tex]f^{-1}(x) = a[/tex] means that [tex]f(a) = x[/tex].

In this problem, it is asked [tex]h^{-1}(-1)[/tex].

  • From the graph, it is taken that at the original function, when [tex]x = 1, y = -1[/tex], hence [tex]h(1) = -1[/tex].
  • Then, applying the inverse function, we have that [tex]h^{-1}(-1) = 1[/tex], and thus 1 is the value of the inverse function.

A similar problem, also involving inverse functions, is given at https://brainly.com/question/23950969